A comparison of the frequency of familial suicide attempts across eating disorder diagnoses - Pisetsky, Emily M. (Int J Eat Disord, 2017)
OBJECTIVE: This study examined the prevalence of reported suicide attempts among family members of individuals with an eating disorder (ED). METHOD: 1870 individuals presenting for ED treatment reported whether their family members ever made a suicide attempt using the Eating Disorders Questionnaire. RESULTS: A lifetime suicide attempt by any family member was reported by 10.8% (n = 202) of the sample and ranged from 7.0% of those with eating disorder not otherwise specified to 16.1% of those with purging disorder. Controlling for age and gender, individuals with bulimia nervosa had a higher prevalence of any familial suicide attempt and mother suicide attempt than individuals with EDNOS; no other differences were observed across ED diagnoses. There were no differences in prevalence of reported suicide attempts made by fathers, brothers, sisters, uncles, or aunts by ED diagnosis. CONCLUSIONS: Findings support a growing literature indicating a familial association between EDs and suicide risk.